Ideology and economy - A historical study of a social democratic newspaper - Engwall, Lars (Uppsala University, 1988)
The study aims to describe the economic and organizational developement of the Swedish local Social Democratic newspaper Värmlands Folkblad from its foundation 1903 until today. The file contains the papers turnaround on a yearly basis for the years 1918 to 1982.

The study aims to describe the economic and organizational developement of the Swedish local Social Democratic newspaper Värmlands Folkblad from its foundation 1903 until today. The file contains the papers turnaround on a yearly basis for the years 1918 to 1982.
Ideologi och ekonomi - En historisk studie av en socialdemokratisk dagstidning
Keywords: Economic systems and development; Ekonomiska system och ekonomisk utveckling; Media; Media; Business/industrial management and organisation; Företags-/industriledning och organisation; Social Sciences; Samhällsvetenskap